STRENGTHENING RELIGIOUS MODERATION FOR STUDENTS THROUGH LITERATURE LITERACY PROGRAM - Leny Sri Wahyuni; Listiana Ikawati (JOURNAL OF LANGUAGE, 2023)
Facts related to religious ways that tend to be radical and extreme can threaten the reason and attitude of the younger generation, including students. Therefore, an innovation study focusses on the positioning of students in order to act as producers against extremist narratives is needed. This can be done with intensive education and mentoring of good and directed writing skills through a literature literacy program with religious moderation perspectives for students. Therefore, this research is aimed to describe the study of innovation through a literature literacy program with religious moderation perspectives at the Darul Ma'arif Cikedung Islamic boarding school, Majalengka. This research is descriptive qualitative research using the case study method. Based on the results of the research, it is found that the understanding of moderation does not have to be conveyed rigidly through classes that tend to be conventional but can also be done through light writing of the literary genre as a form of innovation in the spread of Islam rahmatan lil alamin. This is proven by the results obtained by the Darul Ma'arif students who can manifest their moderate understanding through literary works in the form of short stories.